Educational Development and the Pace of Religious Change: How the Sequence of Institutional Change in China and Japan Shaped the Emergence of Modern Religious Policy (Journal for the Study of Religion and History (JSRH), 2025)
In the mid 1800s, both China and Japan began reform movements in order to face the threat of increasing Western encroachment. Central to that reform were adaptations of the educational systems that helped prepare the revolutionary leaders of the Meiji Restoration in Japan and the Xinhai Revolution in China. As part of the state formation process, each country determined the role that religion would play in the new modern state. The policies each chose were significantly influenced by the educational context out of which those new leaders had emerged. Yet those leaders were shaped by the pace and sequence of educational reform relative to the timing of political revolution. Japanese leadership in the Meiji era reflected the kokugaku and Confucian education they had received. Similarly, Nationalist leadership exhibited the Euro-American educational context, whether threw study abroad or at Western schools at home, in the policy choices they made.